2013
DOI: 10.1186/1475-2891-12-8
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium plus vitamin D3 supplementation facilitated Fat loss in overweight and obese college students with very-low calcium consumption: a randomized controlled trial

Abstract: BackgroundRecent evidence suggests that higher calcium and/or vitamin D intake may be associated with lower body weight and better metabolic health. Due to contradictory findings from intervention trials, we investigated the effect of calcium plus vitamin D3 (calcium+D) supplementation on anthropometric and metabolic profiles during energy restriction in healthy, overweight and obese adults with very-low calcium consumption.MethodsFifty-three subjects were randomly assigned in an open-label, randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 37 publications
5
76
0
4
Order By: Relevance
“…For estimating sample size, we considered type 1 (α) and type 2 errors (β) of 0.05 and 0.20 (power=80%), respectively, and serum insulin levels as a key variable. On the basis of a previous study [18], the SD of serum insulin was 32.2 pmol/l, and the difference in mean (d) of insulin levels was 25.8 pmol/l. We reached the sample size of 25 participants for each group using the suggested formula for parallel clinical trials.…”
Section: Methodsmentioning
confidence: 87%
“…For estimating sample size, we considered type 1 (α) and type 2 errors (β) of 0.05 and 0.20 (power=80%), respectively, and serum insulin levels as a key variable. On the basis of a previous study [18], the SD of serum insulin was 32.2 pmol/l, and the difference in mean (d) of insulin levels was 25.8 pmol/l. We reached the sample size of 25 participants for each group using the suggested formula for parallel clinical trials.…”
Section: Methodsmentioning
confidence: 87%
“…Body composition data were obtained using a multifrequency bioelectrical impedance analyzer (Zeus 9.9 PLUS; Jawon Medical Co., Ltd., Kungsang Bukdo, South Korea) 17. The subjects were asked to avoid eating or drinking anything except water, and the test was performed after full voiding.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary analysis of the Women's Health Initiative study concluded that calcium and vitamin D 3 given in combination decreased the risk of postmenopausal weight gain over an average of 7 years (56) and other prospective studies have shown that weight loss can facilitate an increase in circulating 25(OH)D concentrations over time (57)(58)(59)(60) . Although this evidence appears promising in support of the relationship between vitamin D and weight loss, evidence from intervention studies is less clear (61)(62)(63)(64)(65) . Many of these studies give cholecalciferol with or without calcium and show equivocal results.…”
Section: Prospective and Intervention Studiesmentioning
confidence: 99%